1994
DOI: 10.1039/c39940002143
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II) acetate catalysed hydrosilylation of enamides and N-vinylureas leading to 1-(trialkylsilyl)alkylamine derivatives

Abstract: The [R ~* ( O A C ) ~]catalysed hydrosilylation of enamides and N-vinylureas with dimethylphenylsilane proceeds smoothly in a regio-and site-selective manner to give l-(trialkylsilyl)alkylamine derivatives in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…RhCl(PPh 3 ) 3 was prepared by a published procedure. N -(Silylalkyl)amide 2k was prepared by a reaction similar to that in eq 1 …”
Section: Methodsmentioning
confidence: 99%
“…RhCl(PPh 3 ) 3 was prepared by a published procedure. N -(Silylalkyl)amide 2k was prepared by a reaction similar to that in eq 1 …”
Section: Methodsmentioning
confidence: 99%
“…We have also investigated an alternative approach to ␣-aminosilanes based on a hydrosilylation reaction reported by Murai and Kato,33 who found that N-alkenyl amides and ureas will undergo rhodium acetate-catalyzed hydrosilylation with dimethylphenylsilane to give the ␣-aminosilane product 30 with high regiospecificity (Fig. 15).…”
Section: Hydrosilylationmentioning
confidence: 98%
“…229 double bonds may be employed to promote intramolecular cyclisations of 1,5-dienes, provided an ytterbium catalyst is Intramolecular asymmetric hydrosilylation of 201, using a combination of rhodium(1) with S-BINAP gives the siloxacycle 202 in up to 96% ee.231 Rhodium catalysed hydrosilylation of N-acyl enamines results in introduction of the silyl group a-to the nitrogen atom, as in 203. 232 Asymmetric ketone hydrosilylation may also be achieved by the use of appropriate complexes of rhodium ( I ) ~~~ and a similar asymmetric reduction process of nitrones by the use of a ruthenium-BINAP combination (ee's up to 91%).234 This hydrosilylation process can also be used to prepare silanes which are chiralat silicon; reaction of 1-naphthylphenylsilane with symmetrical ketones, catalysed by a rhodium(1) BINAP catalyst, is reported to give products 204 of up to 99% ee. Subsequent reaction of 204 with methylmagnesium bromide results in conversion to the corresponding chiral silane 205 in equally high ee.…”
Section: Other Classes Of Silicon Reagentmentioning
confidence: 99%